2007
DOI: 10.1371/journal.pone.0000205
|View full text |Cite
|
Sign up to set email alerts
|

Bats' Conquest of a Formidable Foraging Niche: The Myriads of Nocturnally Migrating Songbirds

Abstract: Along food chains, i.e., at different trophic levels, the most abundant taxa often represent exceptional food reservoirs, and are hence the main target of consumers and predators. The capacity of an individual consumer to opportunistically switch towards an abundant food source, for instance, a prey that suddenly becomes available in its environment, may offer such strong selective advantages that ecological innovations may appear and spread rapidly. New predator-prey relationships are likely to evolve even fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 39 publications
(46 reference statements)
2
50
1
1
Order By: Relevance
“…A recently discovered case is the predation of a large aerial hawking bat on night migrating songbirds (Popa-Lisseanu et al 2007). Conversely, here we present evidence for opportunistic predation of a songbird, the great tit (Parus major), on bats.…”
Section: Introductioncontrasting
confidence: 39%
“…A recently discovered case is the predation of a large aerial hawking bat on night migrating songbirds (Popa-Lisseanu et al 2007). Conversely, here we present evidence for opportunistic predation of a songbird, the great tit (Parus major), on bats.…”
Section: Introductioncontrasting
confidence: 39%
“…Stable-isotope analysis of bat tissue has been used in numerous dietary studies (Fleming et al 1993, Voigt and Kelm 2006, Popa-Lisseanu et al 2007, Painter et al 2009, Cryan et al 2012, and also to investigate the origins and migratory movements of bats. (Cryan et al 2004, Cryan et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This can be further linked with the suggestion that distribution of greater noctule closely follows the migration paths and high abundance of passerine birds. As a nocturnal ''ecological equivalent'' of N. lasiopterus, Eleonora's Falcon, Falco eleonorae, catches prey in the air during the autumn migration from Europe to Africa, and switches its diet from mostly large insects to catching migrating birds (Ristow et al 1986, Popa-Lisseanu et al 2007. A few sightings of F. eleonorae were recorded in the Kornati archipelago (Lukač et al 1997), and nests were confirmed on cliffs for islands distant from the coastline (Figure 1, Š ćetarić 2001, Š ćetarić-Legan andPiasevoli 2005, G. Piasevoli personal communication).…”
mentioning
confidence: 99%